Cowpea evapotranspiration modeling using the FAO-56 dual crop coefficient approach for climate-resilient agriculture under deficit irrigation conditions - Karam A. Elzopy; Udayar Pillai Surendran; Ashish K. Chaturvedi; Girish Gopinath; P. Raja; K. Madhava Chandran; Naeem Khan; Mohamed A. Yassin; Mohamed A. Mattar; Ali Salem (Applied Water Science)
Abstract This study evaluated the effects of different irrigation methods, varying levels of water deficit, and irrigation intervals on transpiration, soil evaporation, crop growth, and yield of cowpea (Vigna unguiculata) under field conditions. The assessment was conducted using the food and agriculture organization-56 dual crop coefficient method across seven irrigation treatments. In the I1, I2, and I3 treatments, irrigation was applied through a drip irrigation system at 100%, 80%, and 60% of crop evapotranspiration (ETc), respectively. In contrast, in the I4, I5, and I6 treatments, irrigation was provided at 100% of ETc when soil moisture depletion reached 45%, 60%, and 75% of the management allowed depletion threshold, respectively. The I7 treatment consisted of conventional furrow irrigation applied at four-day intervals. The results revealed that variable irrigation intervals in the I4, I5, and I6 treatments resulted in seasonal soil evaporation (E) savings of 17.4%, 29.9%, and 42.8%, respectively, compared to the treatments receiving frequent irrigation at two-day intervals. Furrow irrigation (I7) doubled the evaporation losses as compared to drip irrigation. Under deficit irrigation in I2 and I3, transpiration (T) decreased by 18.5% and 42.7%, while ETc was reduced by 13.2% and 30.6%, respectively. Conversely, only 4.8% and 16.2% reductions in transpiration were observed under I5 and I6, respectively. The non-frequent irrigation regime in I4, I5, and I6 decreased seasonal ETc by 5.0%, 12.0%, and 23.8%, respectively, whereas furrow irrigation (I7) increased ETc by 28.1%. The highest growth and yield attributes were observed in drip-irrigated I1 and I4 treatments, as confirmed through spectral signatures and vegetation indices. The maximum yield of cowpea (11.57 tons per hectare) was recorded in I4, which was statistically on par with I1 and I7. The lowest yield was observed in the severely water-stressed I3 and I6 treatments. Deficit irrigation in I2 and I3 significantly improved the Water Productivity (WP, kg/m3)–Yield per unit of total crop evapotranspiration, Transpiration Use Efficiency (TrUE, kg/m3)–Yield per unit of transpiration, Irrigation Water productivity (IWP, kg/m3)–Yield per unit of irrigation water applied and Biomass Transpiration Productivity (WPTr, kg/m3)–Biomass per unit of transpiration. The study highlights the potential of deficit irrigation strategies (I2 and I3) to enhance water productivity and efficiency, while non-fixed irrigation intervals (I4, I5, and I6) contribute to reducing soil evaporation losses. Drip irrigation at 100% ETc with a non-fixed irrigation interval (I4) emerged as the most effective treatment, optimizing both yield and water conservation. These findings have significant implications for improving irrigation management in water-scarce regions.